1976
DOI: 10.1002/1097-0142(197605)37:5<2306::aid-cncr2820370521>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A malignant tumor of the vagina resembling synovial sarcoma.A light and electron microscopic study

Abstract: A malignant tumor arising in the upper lateral vaginal mucosa in a 24-year-old white woman, hitherto undescribed in the literature, was studied by light and electron microscopy. The main part of the tumor was epithelioid, forming a tubular or acinar pattern. At the periphery, the tumor cells were more spindly and formed sheets resembling fibrosarcoma. T h e tumor cells contained occasional material positive for mucicarmine, alcian blue, and PAS stains, and the nests of the cells forming acini were surrounded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It is an aggressive soft-tissue tumor arising from mesenchymal or epithelial cells. Although the clinical and pathologic features of vaginal synovial sarcoma have been well documented (44,45), our review of the literature revealed that the MR imaging features have not been documented, to our knowledge.…”
Section: Spindle Cell Synovial Sarcomamentioning
confidence: 78%
“…It is an aggressive soft-tissue tumor arising from mesenchymal or epithelial cells. Although the clinical and pathologic features of vaginal synovial sarcoma have been well documented (44,45), our review of the literature revealed that the MR imaging features have not been documented, to our knowledge.…”
Section: Spindle Cell Synovial Sarcomamentioning
confidence: 78%
“…Our case lacked any mitotic figures and had very well‐circumscribed margins. Benign mixed tumors can also be confused with the extremely rare malignant mixed tumor of the vagina which looks like synovial sarcoma ( 37,38 ) . The lack of tumor circumscription with the presence of cytologic atypia and mitotic activity are features in favor of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Our case lacked any mitotic figures and had very well-circumscribed margins. Benign mixed tumors can also be confused with the extremely rare malignant mixed tumor of the vagina which looks like synovial sarcoma (37,38) . The lack of tumor circumscription with the presence of cytologic atypia and mitotic activity are features in favor of malignancy.…”
Section: Discussionmentioning
confidence: 99%